A prospective study of peripheral arterial diseases in chronic kidney disease patient attending tertiary care hospital Andhra Pradesh - Jawaharlal, Ramswarup K.; Mootha, Vamsi Krishna (International Journal of Advances in Medicine, 2021)
Background: Around 10% populations worldwide develop chronic kidney disease and two million people require frequent dialysis due to it1. Cardiovascular diseases related complications are more common in chronic kidney patients and responsible for greater morbidity and mortality. This study is designed to determine the peripheral artery disease in patients with chronic kidney disease in our clinical setup and risk factor associated with them. Methods: In present study 140 patients with chronic kidney disease were enrolled for this study. Demographic profile of each patient was recorded. Detailed history of patients regarding claudication was taken. Ankle-brachial index was calculated in each patient with CKD for diagnosis of PAD based on American heart association guideline. Results: There was male predominance. History of smocking was present in 80 (57.14%) patients and absent in 60 (42.85%) patients. Symptom of PAD was present in 28 (20%) patients and absent in 114(80%) patients. Ankle-Brachial Index was positive in 38(27.14%) patients and absent in 102 (72.85%) patients. 80 (57.14%) patients were in stage 3 and 24 (17.14%) patients were in stage 4. Diabetes mellitus was present in 26 (18.57%) patients, Hypertension was present in 64 (45.71%), IHD was present in 22 (15.71%) remaining have no risk factor. Conclusions: From present study we can conclude that PAD was common in CKD patients more than 50 years of age and here is male predominance. It is more common in smoker and in most of the patients it was asymptomatic. Prevalence of PAD was 27.14% in CKD patients. In our study PAD was more common in stage 3 CKD and least common in stage 2, and cardiovascular risk factor was more common in PAD patients then CKD in general.